Analisis Hukum Pidana Positif dan Hukum Pidana Islam terhadap Aliran Sesat sebagai Modus Operandi Dalam Melakukan Tindak Pidana di Indonesia - Rizka Hanum Mendrofa; Ramadhan Syahmedi Siregar (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Heretical sects are teachings or activities that deviate from religious norms. Misguided sects that are currently happening a lot both in Indonesia and in the world are sects that violate human rights. Apart from deviating from our spirituality and beliefs in religion, this sect also makes its followers victims of criminal acts by the sect leaders themselves. In collecting data the author uses normative juridical methods. The normative juridical method is library law research by examining library materials or with primary legal materials and secondary legal materials that support the author's research. The results of this study indicate that the modus operandi in committing a crime can be done in the name of religion. where this concerns the problem of our spirituality to God Almighty. This study concludes that deviant sects are also regulated in the Criminal Code where the sanctions for the perpetrators are in accordance with the conditions of the crime they committed. In the perspective of Islamic criminal law, the spread of deviant sects can be as Jarimah Hudud. In Criminal Law, efforts to overcome heretical sects are inseparable from the concept of crime prevention and in the Islamic view by strengthening faith and strengthening monotheism to Allah SWT Keywords : Heretical sects, Modus operandi, Criminal acts